Isolation of a galactose-binding lectin from the venom of the snake Bothrops godmani (Godmann's pit viper). - Lomonte, Bruno (1990)
A galactose-binding lectin, isolated from the venom of B. gotlmani by affinity chromatography . is an acidic protein (pI 4.9) with a subunit mol. wt of about 14,000, occurring mostly as a disulfide-linked dimer of 28,000. A small proportion of lectin appears as a monomer and as a tetramer. The lectin agglutinates erythrocytes from mice, rabbit, cow and human (all ABO types, either Rh positive or negative), but does not agglutinate horse, sheep, goat and snake (Oxybelis aeneus, Colubridae) erythrocytes . The agglutinating activity is inhibited by 1 mM EDTA. The lectin is devoid of lethal, hemorrhagic, myotoxic, proteolytic and phospholipase A2 activities . It is not mitogenic for human peripheral blood mononuclear cells. The only effect observed was amoderate induction of edema in the footpad of mice, with a minimal edema-forming dose of 22 kg. This effect developed rapidly, and was significantly inhibited by i.p . administration of cyproheptadine, a histamine and serotonin antagonist, before injection of the lectin . Despite the edema-forming activity observed, the low concentration of lectin in crude venom, together with its relatively low potency, suggest that this lectin is not a key component in the development of edema following envenomations by B. godrnani.